Universidade Regional do Noroeste do Estado do Rio Grande do Sul - Monique Linhares Barroso; Aline Lopes de Pontes; Karla Maria Carneiro Rolim (Rev Rene, 2015)
Objective: to grasp under the maternal perception the consequences of prematurity in the establishment of the affective bond between adolescent mothers/premature babies. Methods: descriptive exploratory study, of qualitative nature, with the participation of ten teenage mothers whose newborn preterm infants had been hospitalized in neonatal care units. Subjects were interviewed and one obtained identification data and used issues related to the affective bond between mothers and children. Results: mothers have different perceptions about their children’s suffering and consider prematurity a serious problem that hinders the affective bond between mothers/babies. Conclusion: the nursing team must rethink their practices, seeking opportunities for scientific and emotional growth, aiming to promote the mother’s stay in the unit, the establishment of the link between teenage mothers/babies and encouraging mothers to have active participation in the recovery of their children.